Escalating costs of billion-dollar disasters in the US: Climate change necessitates disaster risk reduction - Vijai Bhola; Attila Hertelendy; Alexander Hart; Syafwan Bin Adnan; Gregory Ciottone (The Journal of Climate Change and Health, 2023)
Introduction: The United States (US) spends a staggering amount on costs secondary to natural disasters, over $2 trillion between 1980 and 2021, during which time 15,347 disaster related deaths also occurred [1]. We assess the relationship between CO2, temperature, and the number and economic costs of billion-dollar disaster events in the US during this period. Materials & Methods: Data on the annual number of inflation-adjusted billion-dollar disasters in the US, global CO2 levels, average temperature, and fatalities were obtained from the National Oceanic and Atmospheric Administration (NOAA) for the period 1980–2021. Spearman's correlation (rs) was calculated to analyze the relationship between these variables. Results: Over this 41-year period, CO2 levels, temperature, and the number of billion-dollar disasters in the US all increased and are strongly correlated. The rate of events over this period increased along with increases in CO2 (Spearman's correlation (rs)=0.841) and temperature (rs =0.748). Conclusions: CO2 levels and temperature have increased over the past 4 decades and are strongly positively correlated with the number of and total cost due to billion-dollar disasters. This strong correlation suggests that the annual number of events in the US will continue to increase along with their economic burden, so measures are needed to mitigate those costs. We recommend a focus on Disaster Risk Reduction (DRR) as an immediate cost savings measure, in keeping with United Nations Disaster Risk Reduction and UN Sustainable Development Goals recommendations. Additional research on the healthcare costs associated with natural disasters is needed.